Estrogen receptor expression in normal breast epithelium in invasive ductal carcinoma - Erkinüresin, Taşkın; Demirci, Hakan; Vardar Aker, Fügen (The European Research Journal, 2021)
Objectives: Invasive ductal carcinomas (IDCs) are the most important group of malignant breast tumors and constitute 75-80% of breast carcinomas. While IDCs often present with ductal carcinoma in situ (DCIS), they sometimes include a low level of DCIS or they do not include any accompanying DCIS at all. We planned this study to compare estrogen receptor (ER) expression levels in normal mammary epithelium in IDCs with extensive DCIS (Group I) and IDCs without DCIS (Group II). Methods: Eighty IDC cases selected from among samples that were analyzed in our pathology laboratory. The cases were assessed retrospectively in light of immunohistochemical analysis results and pathology reports. Evaluation of immunohistochemistry: ER positivity in IDC was defined with a nuclear staining of more than 10% of cancer cells regardless of intensity of staining. Presence of cells showing nuclear staining for normal breast epithelium was classified in 4 groups according to their quantity and intensity. These were: 0-None: No staining was observed, 1-Single: One or two positive cells, 2-Dispersed: Dispersed positive cells surrounded by negative cells, 3-Adjoined: 10 or more positive cells contacting each other. Results: Statistically no significant difference was found between Group I and Group II in terms of ER expression. Group I were more prevalent in younger and in the premenopausal period than Group II. Conclusions: According to our study, there was no difference between Group I and Group II in terms of ER expression. But the significantly presence Group I in more young people and in premenopausal women suggests that these carcinomas develop due to high estrogen levels and that Group II develop independently than estrogen. This suggests that these groups may have different carcinogenesis and etiologies. We therefore think that this first study on IDCs with extensive DCIS and IDCs without DCIS should be supported by new research studies.